Low Serum Total Testosterone Is Associated with Non-Alcoholic Fatty Liver Disease in Men but Not in Women with Type 2 Diabetes Mellitus - Xinxin Zhang; Jinfeng Xiao; Qi Liu; Yuanyuan Ye; Weihong Guo; Jingqiu Cui; Qing He; Wenli Feng; Ming Liu (International Journal of Endocrinology)
Aims/Introduction. Sex steroid hormones play a significant role in the progression of cardiovascular and metabolic diseases, including non-alcoholic fatty liver disease (NAFLD). The aim of this cross-sectional study was to explore the associations of testosterone, androstenedione, dehydroepiandrosterone (DHEA), and dehydroepiandrosterone sulfate (DHEAS), with the risk of NAFLD in patients with type 2 diabetes mellitus (T2DM). Materials and Methods. There were 1155 patients with T2DM included in the analysis. Serum levels of total testosterone and the precursors of androgens, including androstenedione, DHEA, and DHEAS, were quantified using liquid chromatography-tandem mass spectrometry assays. Results. The risk of NAFLD decreased as total testosterone concentration increased in men with T2DM. After adjusting for age, current smoking, current drinking, body mass index, duration of T2DM, diastolic blood pressure, total cholesterol, triglycerides, low-density lipoprotein/high-density lipoprotein cholesterol ratio, uric acid, C-reactive protein, and sex hormones in model 4, the adjusted odds ratio (OR) and 95% confidence interval (CI) of NAFLD for tertile3 vs tertile1 was 0.37 (0.17–0.77; P=0.024 for trend). When taken as a continuous variable, this association was still robust in model 4 (OR, 0.58; 95% CI, 0.42–0.80; P<0.05). No significant associations were found between increasing levels of the precursors of androgens and the odds of NAFLD in men with T2DM (all P>0.05). Moreover, women showed no significant associations of total testosterone, androstenedione, DHEA, and DHEAS, with the odds of NAFLD (all P>0.05). Conclusions. Serum total testosterone was independently associated with the risk of NAFLD among men with T2DM. This study highlights the potential role of testosterone as a risk factor for NAFLD in patients with T2DM.